2020
DOI: 10.1016/j.brs.2020.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Two weeks of image-guided left dorsolateral prefrontal cortex repetitive transcranial magnetic stimulation improves smoking cessation: A double-blind, sham-controlled, randomized clinical trial

Abstract: Background: Previous studies have found that repetitive transcranial magnetic stimulation (rTMS) to the left dorsal lateral prefrontal cortex (LDLPFC) transiently reduces smoking craving, decreases cigarette consumption, and increases abstinence rates. Objective: We investigated whether 10 daily MRI-guided rTMS sessions over two weeks to the LDLPFC paired with craving cues could reduce cigarette consumption and induce smoking cessation. Methods: We enrolled 42 treatment-seeking nicotine-dependent smokers (!10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 58 publications
(80 reference statements)
4
39
0
1
Order By: Relevance
“…Future studies to validate and clarify this sex difference are necessary. Brain-based smoking cessation interventions, such as transcranial magnetic stimulation, have been evaluated for smoking cessation ( Li et al, 2017 ) and reduced cigarette consumption and nicotine dependence after stimulation of the insula ( Dinur-Klein et al, 2014 ) or the left dorsolateral prefrontal cortex ( Li et al, 2020 ; Abdelrahman et al, 2021 ). Such interventions may improve their efficacy by targeting different brain regions, and perhaps different subregions of the insula, in men vs women.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies to validate and clarify this sex difference are necessary. Brain-based smoking cessation interventions, such as transcranial magnetic stimulation, have been evaluated for smoking cessation ( Li et al, 2017 ) and reduced cigarette consumption and nicotine dependence after stimulation of the insula ( Dinur-Klein et al, 2014 ) or the left dorsolateral prefrontal cortex ( Li et al, 2020 ; Abdelrahman et al, 2021 ). Such interventions may improve their efficacy by targeting different brain regions, and perhaps different subregions of the insula, in men vs women.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that rTMS is promising treatment option for many neuropsychiatric conditions like depression, 2,24,25 OCD, 28 BD, 36,37 negative symptoms 29 and auditory hallucinations 30,31 in schizophrenia, addiction,s [33][34][35] anxiety and anxiety related disorders, [39][40][41] fibromyalgia, 44,45 chronic pain, 42,43 and dementia/Alzheimer's disease. [46][47][48][49] It is also very important that many studies reported that rTMS causes significant improvement of cognition.…”
Section: Resultsmentioning
confidence: 99%
“…According to a recent study, daily rTMS (MRI-guided) in the left DLPFC for 10 days may reduce cigarette consumption as well as the desire for up to a month and at the same time increases the likelihood of smoking cessation. 34 In addition, rTMS appears to be a promising treatment for cocaine use disorder, as it appears to have a therapeutic role in reducing cocaine use and associated symptoms such as sleep disturbance and other adverse symptoms. 35 Bipolar Disorder rTMS is a promising treatment option for patients with both monopolar and bipolar depression.…”
Section: Addictionsmentioning
confidence: 99%
“…However, there is currently no widely adopted E-field dosing approach or consensus on the optimal E-field dosing threshold. Here we investigate four E-field modeling methods that could be used to prospectively dose prefrontal TMS, demonstrating the benefits and drawbacks of each approach through modeling on our 38 previously acquired scans [8](Fig. 1AeD; Supplementary Section 1 for E-field modeling methods).…”
Section: Dear Editormentioning
confidence: 99%